Factors of independent of activities of daily living among osteoarthritis elderly - Hariza Adnani; Anna Nur Hikmawati; Siranee Sihapark; Dwi Suharyanta; Dwi Widiyaningsih (Intelektual Pustaka Media Utama, 2022)
The aim of this cross-sectional study was to determine the relationship between ability to carry out activities of daily living (ADL) independently and functional ability, mental status, exercise habits, and other factors, among elderly people with osteoarthritis (OA) at Pleret Bantul, Indonesia. Measures included Katz Index of Independence in ADL, Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and the Short portable mental status questionnaire (SPMSQ). Chi-square analyses odds ratios (OR) were calculated. The study results showed that the ADL independence among the sample was associated with younger age OR=.347; 95% CI =.253-.477), exercise habit OR=7.07; 95% CI=2.86-17.47) and functional ability (OR=2.34; 95% CI=1.82-3.01). There was no relationship between living situation or mental status and ADL. These findings can be used as information to design programs to support independence in ADLs among elderly persons with OA in Indonesia.